All-fiber Tm-Ho codoped laser operating at 1700 nm - Park, Jaedeok; Ryu, Siheon; Yeom, Dong Il (Current Optics and Photonics, 2018)
We demonstrate continuous-wave operation of an all-fiber thulium-holmium codoped laser operating at a wavelength of 1706.3 nm. To realize laser operation in the short-wavelength region of the emission-band edge of thulium in silica fiber, we employ fiber Bragg gratings having resonant reflection at a wavelength around 1700 nm as a wavelength-selective mirror in an all-fiber cavity scheme. We first examine the performance of the laser by adjusting the central wavelength of the in-band pump source. Although a pump source possessing a longer wavelength is observed to provide reduced laser threshold power and increased slope efficiency, because of the characteristics of spectral response in the gain fiber, we find that the optimal pump wavelength is 1565 nm to obtain maximum laser output power for a given system. We further explore the properties of the laser by varying the fiber gain length from 1 m to 1.4 m, for the purpose of power scaling. It is revealed that the laser shows optimal performance in terms of output power and slope efficiency at a gain length of 1.3 m, where we obtain a maximum output power of 249 mW for an applied pump power of 2.1 W. A maximum slope efficiency is also estimated to be 23% under these conditions.
Keywords: Central wavelength; Co-doped; Continuous wave operation; Maximum output power; Medical lasers; Optimal performance; Resonant reflection; Wavelength-selective; Fiber Bragg gratings; Fiber laser; Medical laser; Tm-Ho codoped laser